The ANALYSIS OF GAS STATION SERVICES AND THE CORRELATION ON CUSTOMER SATISFACTION: Case Study on SPBU in Bandung - Santi Lina; Rutman Lumbantoruan SE., MM (Fakultas Ekonomi Universitas Kristen Indonesia, 2013)
The gas station is a service business that has a small price elasticity, because the fuel is included important needs that must be met for some people. So, the service should not affect the level of sales, but the phenomenon that the opposite is true. The expected goal of this paper is to determine how the services provided by a gas station to the satisfaction of its customers, how management efforts to improve its services, and to analyze the relationship between services performed for customers. Research methods that will be used is descriptive method, that is by doing data collection, inventory, process, to present the results with interpretation, and provide an overview of the relationship between the variables studied. And eventually will get a clear picture of the subject matter studied. From the analysis results obtained correlation coefficient of 0.7089 (positive correlation) with a coefficient of determination 50.53%. The results of hypothesis testing provides a strong and positive relationship between the quality of service provided to customer satisfaction. If the quality of services provided is high enough, the level of customer satisfaction will also increase, and vice versa.